Domain-general and domain-preferential neural correlates underlying empathy towards physical pain, emotional situation and emotional faces: An ALE meta-analysis. (3rd February 2020) - Ding, Rui; Ren, Jie; Li, Shuaixia; Zhu, Xiaowen; Zhang, Keye; Luo, Wenbo
Abstract: Empathy is essential for social interactions and individual development. Through the empathy field, the domain could be divided into three subgroups according to the stimulus materials adopted in tasks: empathy towards physical pain (PhyE), empathy towards emotional situations (ESuE) and towards emotional faces (ExpE). By far, no empirical studies directly compared the neural correlates underlying three sub-domains. The current study, therefore, utilized ALE meta-analysis to identify the general and distinct neural correlates underlying three sub-domains of empathy. The results revealed the conjunction in bilateral supplementary motor areas which were generally activated across three sub-domains. Preferential correlates for PhyE were found in bilateral IPL, left middle cingulate cortex and left anterior insula, which were associated with pain, action and somatosensory functions. Left middle temporal gyrus was found to be preferentially engaged for ESuE. And the preferential activations for ExpE were identified in right amygdala and right dorsal lateral prefrontal cortex, the regions of which were statistically associated with functional Neurosynth terms "facial expression", "face", "emotion" and "social". Through the current meta-analyses, we firstly indicated that the domain-general and domain-preferential neural correlates potentially exist to underlie the processing of empathy evoked by different types of stimuli. Highlights: A large-scale ALE meta-analysis including 103 empathy-related studies was conducted. Domain-general neural correlates underlying empathy were revealed in supplementary motor area. Activation convergence of empathy for physical pain, emotional situations and emotional faces was indicated to be different. Domain-preferential correlates were supported by functional characterization analysis using Neurosynth terms.